Persistent RCSMA: A MAC Protocol for a Distributed Cooperative ARQ Scheme in Wireless Networks. (12th May 2008) - Alonso-Zárate Alonso-Zárate, J. J.; Kartsakli Kartsakli, E. E.; Verikoukis Verikoukis, Ch. Ch.; Alonso Alonso, L. L.
Abstract : The persistent relay carrier sensing multiple access (PRCSMA) protocol is presented in this paper as a novel medium access control (MAC) protocol that allows for the execution of a distributed cooperative automatic retransmission request (ARQ) scheme in IEEE 802.11 wireless networks. The underlying idea of the PRCSMA protocol is to modify the basic rules of the IEEE 802.11 MAC protocol to execute a distributed cooperative ARQ scheme in wireless networks in order to enhance their performance and to extend coverage. A closed formulation of the distributed cooperative ARQ average packet transmission delay in a saturated network is derived in the paper. The analytical equations are then used to evaluate the performance of the protocol under different network configurations. Both the accuracy of the analysis and the performance evaluation of the protocol are supported and validated through computer simulations.